Influência da magnitude, volatilidade e crescimento da geração de caixa no endividamento das empresas na américa latina - Silveira, Arthur Garcia (2021)
The dissertation seeks to understand the relationship between business leverage and business cash generation factors: magnitude (the intensity of generating cash), volatility (the oscillation of cash generation) and growth (increase in cash generation). The objective is to understand whether these three factors directly impact the level of indebtedness of Latin American companies over time. While the Pecking Order theory seeks the opposite relationship between the company's profitability and its leverage, the Trade-off theory assumes that there is a positive relationship and the finding of an optimal point for contracting debts. The research presents the modified trade-off concept, which seeks to understand the relationship between business leverage decisions and cash. There is an understanding that companies incur more debt if they have a stable, growing and volume of cash generation that allows them to pay off financial expenses successfully. It is assumed that a company's debt potential is linked to the profitability that managers are able to print in operations. The higher forecast of cash generation in the future would allow managers to incur greater debts than current ones. Debt was considered the dependent variable and two aspects were considered: net and gross debt. Cash generation proxies are used, such as ROA (return on assets), ROIC (return on invested capital) and Market to Book Value, in dollarized values. The use of panel data was adopted using the economical software Stata®. The companies' balance sheets were collected through the Capital IQ® system. The tests carried out demonstrate the relevance of the proposed hypotheses and that the magnitude, volatility and cash growth explain the increase or decrease in corporate leverage. It is noted that the frequent economic crises in Latin America directly impact on leverage, in the opposite direction to what was expected. The growth in cash, as well as the magnitude of how this occurs,